Disorder-driven non-Fermi liquid behavior in itinerant ferromagnet α-Co5Ge3. (10th January 2020) - Song, Meng; Xian, Cong; Wang, Yihao; Song, Jiangpeng; Li, Zhihao; Ling, Langsheng; Zhang, Lei; Han, Yuyan; Cao, Liang; Xiong, Yimin
Abstract: The physical properties of itinerant ferromagnet -Co5 Ge3 with both strong disorder and spin fluctuations was studied. The dc and ac susceptibility show that both spin fluctuations and disorder dominate the physical properties. In the spin glass phase, with a coexisting ferromagnetic state ( 30 K), both non-Fermi liquid behavior and large exponent of scaling relation of are observed and attributed to the spin fluctuations and disorder induced by cobalt defects. Upon the increase of external field, Fermi liquid behavior restores due to the suppression of spin fluctuations and disorder. In addition, a large anomalous Hall coefficient R s is observed. Our results suggest that -Co5 Ge3 is a typical itinerant ferromagnet to explore the interplay of disorder and spin fluctuations.